Analisis Tokoh Pada Film “Penyalin Cahaya” sebagai Korban Pelecehan Seksual Menggunakan Teori Kebungkaman - Niken Pramudya Rahmadi; Raden Aditya Rizky Yudhistira (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2024)
Film is a mass media that can influence people's mindset through the message it wants to convey. The film "Penyalin Cahaya" tells the story of Suryani, Farah, and Tariq, who experienced sexual harassment by a fellow Matahari Theater group member, Rama. Rama is described as a figure who has a powerful relationship with the university. This article uses a descriptive qualitative research method. The data collection technique used in this article is the listen-and-note method. The theory used in this article is the Theory of Silence by Edwin Arderner and Shirley Arderner. The purpose of this study is to determine the reasons for the silence experienced by victims of sexual harassment in the film "Penyalin Cahaya." The results of the analysis of the film "Penyalin Cahaya" using the Theory of Silence obtained that the cause of silence in women and men is the lower class, which does not have the power to defend themselves. The existence of authority is the main factor in silence in the film "Penyalin Cahaya." Keywords: Film, Sexual Harassment, Muted